The Addition of Dextrose to the Preparation of Culture Media from Earthworm Juice (Lumbricus rubellus) for the Production of Saccharomyces cerevisiae FNCC 3012 Inoculum (Indonesian Society for microbiology, 2018)
Saccharomyces cerevisiae is one of the commonly used yeast for bioethanol production. It can be produced by growing it in a culture medium containing nitrogen and carbon. Earthworms (Lumbricus rubellus) are high in protein and have a relatively low price that can be used as a source of nitrogen for S. cerevisiae FNCC 3012. Dextrose is used as a carbon source. The objectives of the study were to determine the comparison of the growth rate of S. cerevisiae FNCC 3012 to the earthworm juice and commercial media (malt extract, meat extract, and yeast extract). The highest yield of S. cerevisiae FNCC 3012 cells were produced on the earthworm juice medium with 1% dextrose addition. The maximum specific growth rate (Î¼max) and the saturation constant (Ks) about 3,4.h-1 and 3,1 g.l-1, respectively.